Estimation of zinc and iron levels in the serum and hair of women with androgenetic alopecia: Case-control study - Samer A Dhaher; Abdulla A Yacoub; Ausama Ayob Jacob (Wolters Kluwer Medknow Publications, 2018)
Background: Although female androgenetic alopecia (FAGA) occurs in genetically susceptible women, some trace elements may play an important role. Aim of the Study: This study aimed to evaluate serum and hair zinc and iron levels in patients with FAGA and to compare the findings with normal controls. Patients and Methods: A case-control study that was conducted at Dermatology Clinic in Basra General Hospital, Basra, Iraq. The participants were divided into two groups: The first group consisted of 27 women with FAGA and the second was age-matched 28 healthy women control group. The serum and hair zinc and iron assays were done for all participants. Results: Both hair and serum zinc levels in FAGA group were significantly lower than that in the control (103.4±25.5 ppm vs. 143.5±33.1 ppm for hair and 65.6±14.2 μg/dl vs. 128.4±41.4 μg/dl for serum). Hair iron level in FAGA was significantly lower than in control (17.9±3.8 ppm vs. 26.9±7.4 ppm, P>0.05). Serum iron level in FAGA group was lower than in the control, but it was not significant statistically (88.9±22.3 μg/dl vs. 100.9±18.9 μg/dl). Except for the hair iron, there was no significant correlation between zinc and iron concentrations in hair and serum with severity of alopecia. Conclusions: Zinc and iron levels in serum and hair were lower in FAGA compared to that of normal individuals indicating that trace elements might play an important role in the etiopathogenesis of FAGA.